2012
DOI: 10.1177/0309364612450577
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms to absorb load in amputee running

Abstract: Background: We aimed to determine if a shock absorbing pylon (SAP) influenced the ground reaction force characteristics and the shock absorbing mechanisms compared to a rigid pylon (Rigid) during the loading phase in running. Objectives: To determine if the SAP influences the mechanisms of loading compared to the Rigid condition. Study Design: A convenience sample of transtibial amputees participated in a laboratory-based study. The prosthetic set-up was randomly altered fd\sdsd. Methods: Five recreationally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Although the details of these studies were unclear in a number of cases, many were performed within a laboratory or rehabilitation facility, [48][49][50][51] with the assistance of a certified prosthetist to undertake the fitting and alignment of prostheses. [48][49][50][52][53][54][55] Despite observations of minor trends, the vast majority of studies were suggestive that SAPs show no strong effect for a difference in the ability to attenuate shock as compared to rigid pylons among transtibial amputees while undertaking different modes of activity, including walking, running and stepping down from an elevated platform. [47][48][49][50][53][54][55] Some studies did report isolated but significant differences in group variables, including a reduction in knee flexion upon initial contact when fitted with a SAP and while walking at a controlled speed, 48 as well as differences in select variables among individual participants.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the details of these studies were unclear in a number of cases, many were performed within a laboratory or rehabilitation facility, [48][49][50][51] with the assistance of a certified prosthetist to undertake the fitting and alignment of prostheses. [48][49][50][52][53][54][55] Despite observations of minor trends, the vast majority of studies were suggestive that SAPs show no strong effect for a difference in the ability to attenuate shock as compared to rigid pylons among transtibial amputees while undertaking different modes of activity, including walking, running and stepping down from an elevated platform. [47][48][49][50][53][54][55] Some studies did report isolated but significant differences in group variables, including a reduction in knee flexion upon initial contact when fitted with a SAP and while walking at a controlled speed, 48 as well as differences in select variables among individual participants.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…[48][49][50][52][53][54][55] Despite observations of minor trends, the vast majority of studies were suggestive that SAPs show no strong effect for a difference in the ability to attenuate shock as compared to rigid pylons among transtibial amputees while undertaking different modes of activity, including walking, running and stepping down from an elevated platform. [47][48][49][50][53][54][55] Some studies did report isolated but significant differences in group variables, including a reduction in knee flexion upon initial contact when fitted with a SAP and while walking at a controlled speed, 48 as well as differences in select variables among individual participants. 51,55 These findings, however, were not consistent with the overall trend of the included studies.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heel marker displacement data in the forward direction were used to calculate step length, which in turn was used to calculate running speed (step length/step time). Stance was defined by a vertical GRF threshold of 10 N [12] and divided into braking and propulsion when horizontal GRF equalled zero. Peak vertical (pVF), braking (pBF) and propulsive (pPF) GRF (N.kg -1 ) were extracted and horizontal braking (BI), propulsion (PI) and vertical impulses (VI) calculated by trapezoidal-rule integration.…”
Section: Methodsmentioning
confidence: 99%
“…It follows that stiffness properties of the prosthetic limb may also serve many of these same functions. However, contrary to expectations, previous gait studies have not demonstrated that "shock absorbing" prosthetic components have an appreciable effect on ground reaction force (GRF) profiles [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%